2008
DOI: 10.1084/jem.20081398
|View full text |Cite
|
Sign up to set email alerts
|

Tim-3 expression defines a novel population of dysfunctional T cells with highly elevated frequencies in progressive HIV-1 infection

Abstract: Progressive loss of T cell functionality is a hallmark of chronic infection with human immunodeficiency virus 1 (HIV-1). We have identified a novel population of dysfunctional T cells marked by surface expression of the glycoprotein Tim-3. The frequency of this population was increased in HIV-1–infected individuals to a mean of 49.4 ± SD 12.9% of CD8+ T cells expressing Tim-3 in HIV-1–infected chronic progressors versus 28.5 ± 6.8% in HIV-1–uninfected individuals. Levels of Tim-3 expression on T cells from HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

56
697
7
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 666 publications
(761 citation statements)
references
References 53 publications
56
697
7
1
Order By: Relevance
“…Tim-3, as an important immune regulatory molecule, is expressed on effector Th1 cells and Tc1 cells (8)(9)(10)(11)(12)(13)(14), both of which play important roles in the immune response to HBV. However, whether Tim-3 plays a role in the development of HBV infection still remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Tim-3, as an important immune regulatory molecule, is expressed on effector Th1 cells and Tc1 cells (8)(9)(10)(11)(12)(13)(14), both of which play important roles in the immune response to HBV. However, whether Tim-3 plays a role in the development of HBV infection still remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…As a ligand for Tim-3, galectin-9 is widely distributed in various tissues and is particularly abundant in the liver (29). Previous studies have shown that Tim-3-galectin-9 pathway modulates T cell secretion of IFN- (9,13,14), which is of particular importance to immunity against viral infection. Consistent with these reports, our data verified the simultaneous staining of Tim-3 and IFN- in CD8 + T cells ( Figures 2 and 4), which might explain why Tim-3 pathway influences IFN- production from CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exhausted T cells have also been identified in different viral infections, such as HIV and hepatitis A and B virus (Sharpe et al ., 2007; Keir et al ., 2008). Several previous studies of LCMV, HIV, and HCV infections have suggested that Tim‐3 is another inhibitory marker of exhausted T cells (Jones et al ., 2008; Golden‐Mason et al ., 2009; Jin et al .,2010). Tim‐3 was initially identified in IFN‐γ‐secreting Th1 cells and CD8 + T cytotoxic type 1 (Tc1) cells (Monney et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%